Overdensities of 24 µ m sources in the vicinities of high-redshift radio galaxies - Mayo, J.; Vernet, J.; De Breuck, C.; Galametz, A.; Seymour, Nick; Stern, D. (2012)
We present a statistical study of the environments of 63 high-redshift radio galaxies (HzRGs) between redshifts 1 ≤ z ≤ 5.2, using the 24 μm waveband of the MIPS instrument aboard the Spitzer Space Telescope. Using a counts-in-cell analysis, a statistically significant source overdensity is found in 1.75′ radius circular cells centred on the HzRGs when compared to reference fields. We report an average overdensity of δ 1 (=Ntarget/Nreference) = 2.2 ± 1.2 at a flux density cut of f24 μm = 0.3 mJy. This result implies that HzRGs are likely to lie in protoclusters of active and star-forming galaxies at high redshift. Over 95% of our targeted HzRGs lie in higher than average density fields. Further, 20 (32%) of our selected fields are found to be overdense to at least a 3σ significance, of which 9 are newly identified protocluster candidates. We observe a weak correlation between redshift and 24 μm   source density, and discuss the populations being probed at different redshifts. In our uniformly selected sample, which was designed to cover two orders of magnitude in radio luminosity throughout z = 1−4, we find that the 24 μm   source density does not depend on radio luminosity. We also compare this result with recent work describing IRAC source overdensities around the same HzRGs and find correlations between the results.